(untitled) (Journal of Parents and Teachers, 2025)
The article answers the question of who a student would like to form a class group with, taking into account factors such as friendship and technical assistance. Therefore, there are numerous variables that teacher-tutors must consider when developing Curricular Learning in Groups, and these variables are described in the article.